Population-based study of Helicobacter pylori infection and antibiotic resistance in Bhutan - Ratha-korn Vilaichone (International Journal of Infectious Diseases, 2020)
Objectives: Bhutan suffers from a high prevalence of Helicobacter pylori (H. pylori) infection and gastric cancer-related mortality. In preparation for a countrywide H. pylori eradication program, the antibiotic resistance patterns of H. pylori infection were surveyed in different geographical regions. Methods: Dyspeptic patients in 6 districts including Thimphu, Punakha, Wangdue, Trongsa, Bumthang, and Haa underwent upper gastrointestinal endoscopy during GASTROCAMP and were enrolled between December 2010 and April 2015. Gastric biopsies were obtained for rapid urease test, histopathology, and H. pylori culture. Antimicrobial susceptibility testing was later performed if the culture was positive. Results: A total of 1178 patients were surveyed. The overall H. pylori infection in Bhutan was 66.2%. Punakha had the highest prevalence of H. pylori infection (85.6%). Thimphu and Punakha (city areas) had higher prevalence of H. pylori infection than rural districts (73.5% vs 63.3%, OR = 1.61, 95% CI 1.22–2.13, p = 0.0008). There were 357 patients (30.3%) with positive H. pylori culture completed antimicrobial susceptibility testing. The mean age was 40.5 years with female predominance (57.1%). No amoxicillin resistant strains were found. Metronidazole resistance was 81% followed by levofloxacin resistance (8.1%). Clarithromycin (2%) and tetracycline (0.6%) resistance was rare except in Thimphu, the capital city (10%) vs 0% in rural areas, p < 0.001. The metronidazole resistance rate remained stable at approximately 80% during the past 5 years of study. Levofloxacin-resistant strains gradually rose from 5.3% in 2010 to 9.9% in 2015. Conclusions: Bhutan had a high prevalence of H. pylori infection. Metronidazole resistance was extremely high, whereas clarithromycin resistance was quite low in this specific area. Antibiotic resistance pattern could be good evidence for guiding a proper treatment regimen for H. pylori infection in Bhutan.